PELUANG DAN TANTANGAN AGEN DALAM MENINGKATKAN NASABAH ASURANSI SYARIAH (STUDI PADA PERUSAHAAN ASURANSI SYARIAH BUMI PUTERA CABANG JAMBI) - Rani; Hansen Rusliani; Refky Fielnanda (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to determine the effect of the opportunities and challenges of agents in marketing sharia insurance products in Bumi Putra Jambi. This type of research is qualitative research. The data used is primary data obtained from the Bumi Putra Jambi company. The population is 463 customers during 2010-2022. The analysis used is swot analysis, swot analysis is the identification of various factors systematically to formulate company strategy. Strength (strength), weakness (weakness), Opportunity (opportunity) and threat (threat) are the company's strategic factors that need to be analyzed in the current conditions. The results of the study used strength (1.38), weakness (1.26), opportunity (1.61), and threat (0.93). So it can be concluded that the aopportunities and challenges have the same risk, so the Bumi Putra Jambi company must prepare the right strategy for agents in increasing customers and marketing sharia insurance products.